PENERAPAN PEMBELAJARAN LURING SISTEM SHIFT (GANJIL GENAP) PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ERA NEW NORMAL DI SD NEGERI 61 KOTA BENGKULU - Arfai; Satria, Irwan; Utami, Intan (JPT : Jurnal Pendidikan Tematik, 2021)
The problem in this research is that the spread of the corona virus has occurred in various areas in Bengkulu Province which has an impact on education, especially in the learning process which has changed from face-to-face learning to a shift learning system. The purpose of this study is to describe how the Application of Offline Learning Shift System (Odd Even) in Islamic Religious Education Learning in the New Normal Era and the positive and negative impacts of shift learning in SD Negeri 61 Bengkulu City. The research method used is descriptive qualitative by means of field research, and uses 3 data collection techniques, namely: Observation, interviews and documentation. The location of this research is at SD Negeri 61 Bengkulu City, precisely on Jalan Timur Indah Rt 06 Singaran Pati District, Bengkulu City. The results of this study are to determine the application of the Shift System Offline Learning (Odd Even) in Islamic Religious Education Learning in the New Normal Era at SD Negeri 61 Bengkulu City.